2018
DOI: 10.1371/journal.pone.0191769
|View full text |Cite
|
Sign up to set email alerts
|

Muscle strength and regional lean body mass influence on mineral bone health in young male adults

Abstract: The relationship between muscle strength and bone mineral content (BMC) and bone mineral density (BMD) is supposed from the assumption of the mechanical stress influence on bone tissue metabolism. However, the direct relationship is not well established in younger men, since the enhancement of force able to produce effective changes in bone health, still needs to be further studied. This study aimed to analyze the influence of muscle strength on BMC and BMD in undergraduate students. Thirty six men (24.9 ± 8.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…These results are in contrast with previously reported findings, where WBB athletes ( n = 38) displayed decreases in BF% from the pre- to post-season, ranging from −0.8% to −1.4% [ 1 , 9 , 10 ], and increases in FFM and BM in elite junior WBB players ( n = 9) [ 15 ]. The reduction in FFM observed in the current study is of concern, as previous literature has shown a correlation between FFM and bone mineral density [ 17 ], strength [ 18 , 19 ], speed [ 20 ], and power [ 18 , 21 ]. Reductions in FFM across seasons were also observed in NCAA Division I collegiate softball athletes [ 17 ], thus signifying an ongoing concern for women athletes in regard to maintaining FFM.…”
Section: Discussionmentioning
confidence: 67%
“…These results are in contrast with previously reported findings, where WBB athletes ( n = 38) displayed decreases in BF% from the pre- to post-season, ranging from −0.8% to −1.4% [ 1 , 9 , 10 ], and increases in FFM and BM in elite junior WBB players ( n = 9) [ 15 ]. The reduction in FFM observed in the current study is of concern, as previous literature has shown a correlation between FFM and bone mineral density [ 17 ], strength [ 18 , 19 ], speed [ 20 ], and power [ 18 , 21 ]. Reductions in FFM across seasons were also observed in NCAA Division I collegiate softball athletes [ 17 ], thus signifying an ongoing concern for women athletes in regard to maintaining FFM.…”
Section: Discussionmentioning
confidence: 67%
“…Grip strength is currently much easier to measure, thus has greater potential than would isokinetic dynamometry for incorporating into clinical practice [36]. Nonetheless, the relationship between muscle strength and LBM (whole-body or regional) is well stated [37]. This relationship has been found to be stronger (R 2 = 0.70) when the leg strength is not isometric, but isotonic [38].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a statistically significant relationship was found between Arms aBMD and Appendicular LSTMI, which remained significant even after adjusting for CF experience. LSTMI has been positively associated with aBMD at the WB- and regional levels in young men [ 25 , 26 ], indicating that increasing skeletal muscle mass may contribute to increased aBMD at the upper limb. The hypothesis that the non-weight bearing parts of the skeleton respond to CF participation in a dose-dependent manner deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%